EFFECTIVENESS OF ACCURATE ACCOUNTING SOFTWARE IMPLEMENTATION IN PREPARING FINANCIAL STATEMENTS (CASE STUDY AT PT KARYA MULIA LENTERA PERSADA) - Arep, M.Nur Nama; Lating, Ade Irma Suryani (International Journal of Accounting Innovation, 2025)
Objective: This study was conducted to determine the effectiveness of the application of Accurate Accounting Software in preparing financial reports at PT Karya Mulia Lentera Persada. Method: This type of research uses a qualitative descriptive method with a case study approach. The data used are primary and secondary data obtained through observation, interviews with 3 informants, literature research and documentation. The validity of the information was assessed using data source triangulation techniques. Results: The results of this study state that: The application of Accurate Accounting Software in preparing the financial statements of PT Karya Mulia Lentera Persada runs effectively, as seen from the alignment of the system with all financial activities of the company. Novelty: The novelty of this research is that PT Karya Mulia Lentera Persada has never done any study on the effectiveness of the application of Accurate Accounting Software in preparing its financial statements The effectiveness of Accurate Accounting Software implementation is assessed from the quality of the integrated system, relevant and accurate information, ease of use, satisfaction and quality of service, and a positive impact on individual and company performance.